Family Empowerment in Efforts to Reduce Stunting in Bone Regency, South Sulawesi - Jeddawi, Murtir; Nain, Umar; Ibrahim, Suaib (Journal La Sociale, 2024)
The aim of this research is to identify and analyze effective family empowerment strategies in an effort to reduce stunting rates in Bone Regency, South Sulawesi. This research uses an exploratory qualitative method. The research results show that empowerment strategies that increase parents' knowledge and skills about nutrition, exclusive breastfeeding, hygiene and sanitation can be effective in reducing stunting and improving children's overall welfare. To reduce the stunting rate in Bone Regency, family empowerment is the main key. This includes understanding stunting, healthy nutrition practices, and optimal childcare.